Musiikkiterapiaprosessin merkittävät tekijät ja merkittävät hetket päihteettömän elämäntavan tukijoina - Hairo-Lax, Ulla (Sibelius-Akatemia, 2005)
This dissertation examines the meanings that alcohol addicted clients gave to the group music therapy process. One the one hand, it focuses on the meanings given to events inside the therapy process, and on the other, to the meanings clients gave to the process in terms of their life context. From the viewpoint of the client, this study may possibly gain information on ways of developing and putting into practice a music therapy which supports an intoxicant-free way of life. The data analysed in this study consists of 17 music therapy client interviews. A thematic interview method was used and analysis of the interviews was carried out based on the grounded theory method. The theoretical point of departure of this data oriented study is Lincoln's and Guba's naturalistic paradigm. In the course of the research process, significant moments were selected as a supporting frame of reference. In this study, those moments became the focus of the analysis and refer to intensive and powerful moments experienced by the clients. The other important category found in the analysis was one of significant factors. These refer to the factors affecting the therapy process in the long term. Both the significant moments and the significant factors were experienced either as helpful or hindering to the music therapy process. Different group music therapy techniques alongside the physio-acoustic method were used in the therapy groups. Various art forms were also amongst the methods included. The therapy given can be described predominantly as humanistic. The main goal, then, is the growth of the individual's own developmental potential. The results centre upon the idea that the crucial meaning of music therapy is to help and, through the influence of music, to gain a recognition of those factors which form our quality of life and enhance our holistic well-being, as well as to add those factors to the clients life instead of intoxicants. Music therapy produced, in the interviewees, experiences that exhibited characteristics of a strong feeling of presence, and deep experiencing. Moreover, when offering a positive and meaningful weekly programme, the therapy worked for some clients as a regulator and supporter. Both reciprocal action and interpersonal communication between the client and therapist and the group members were found to be supporting factors. The growth of personal resources manifested itself in better ways of life control; finding new stimuli, the strengthening of initiative and courage as well as a clarification of values. Learning to relax and becoming more aware of one's own physical condition improved the physical state. Active self-processing and a more spontaneous ability to express emotions affected mental health positively. The study also shows how changes in mental health were affected by higher spirits, better self-esteem and improved social relationships with those nearest. The music therapy carried out in this research can be put into practice either as an independent form of rehabilitation or as part of a larger rehabilitation programme. It appears to be especially suitable for those with arts as a favoured means of expression. The study shows how music therapy can be a comprehensive form of rehabilitation for a client committed to the therapy. It takes into account personal life context, may contribute to it qualitatively and in that way could possibly enrich a person's life content. One of the special contributions of music therapy is to procure strong experiences in the form of significant moments. Such moments have aided the music therapy process and have an aspect of well-being that defines a vital and satisfying life.

Tässä väitöskirjassa tarkastellaan päihdeongelmaisten terapia-asiakkaiden ryhmämuotoiselle musiikkiterapiaprosessille antamia merkityksiä. Työ keskittyy yhtäältä musiikkiterapiaistuntojen sisäisille tapahtumille annettujen merkitysten tarkasteluun. Toisaalta keskiössä ovat ne merkitykset, joita musiikkiterapiaprosessi saa kunkin asiakkaan elämänkokonaisuudessa. Väitöskirja tuo kuuluviin päihdeasiakkaiden äänen ja voi siten heidän näkökulmastaan lisätä tietoa päihteetöntä elämäntapaa tukevan musiikkiterapian toteutus- ja kehittämismahdollisuuksista. Tämän laadullisen tutkimuksen analysoidun aineiston muodostavat 17 terapia-asiakkaan haastattelut. Haastattelut tehtiin teemahaastatteluna ja niiden analyysi suoritettiin grounded theory -lähestymistavan mukaisesti. Aineistolähtöisen tutkimuksen teoreettisena perustana oli Lincolnin ja Guban naturalistinen paradigma. Tutkimusprosessin aikana analyysin tueksi valikoitui merkittävät hetket –viitekehys. Tässä tutkimuksessa se tarkoittaa, että keskeiseksi tarkastelun kohteeksi nousivat tiivistyneiksi ja voimallisiksi koetut hetket, jotka toimivat musiikkiterapiaprosessia auttavina tai hidastavina. Merkittävät hetket saivat rinnalleen merkittävät tekijät, joilla tässä tarkoitetaan asiakkaiden kokemuksia prosessiin pitkällä aikavälillä vaikuttavista tekijöistä. Tutkimuksen ryhmissä käytettiin erilaisia ryhmämusiikkiterapian työtapoja sekä fysioakustista menetelmää. Niitä yhdistettiin taidetta monipuolisesti hyödyntäviin työtapoihin. Terapeuttien työskentelyotetta voi kuvailla humanistiseksi, jolloin tärkeänä tavoitteena on ihmisen kasvu kohti omaa potentiaaliaan. Tutkimus osoittaa, että musiikkiterapian keskeinen merkitys on musiikin tuella auttaa kokonaisvaltaista hyvinvointia edistävien elämänsisällöllisten tekijöiden havaitsemisessa ja niiden lisäämisessä päihdeongelmaisen asiakkaan elämään päihteen sijasta. Musiikkiterapia tuotti haastatelluille tutkimusasiakkaille elämyksiä, joille oli ominaista vahva läsnäolo ja syvä kokeminen. Musiikkiterapia toimi myös rytmittäjänä ja tukijana tarjotessaan myönteiseksi ja mielekkääksi koettua säännöllistä ohjelmaa. Rakentava vuorovaikutus sekä terapeutin että vertaisryhmän jäsenten kesken toimivat tukena prosessissa. Musiikkiterapiaprosessin aikana voimavarojen lisääntyminen ilmeni elämänhallintakeinojen ja uusien virikkeiden löytymisenä, oma-aloitteisuuden ja rohkeuden kasvamisena sekä arvojen selkiytymisenä. Kehon tilan tiedostaminen ja rentoutuminen kohensivat fyysistä tilaa. Aktiivinen itseprosessointi ja tunteiden ilmaisun helpottuminen vaikuttivat myönteisesti henkiseen hyvinvointiin. Tätä edistivät myös mielialan ja itsetunnon koheneminen sekä tärkeiden ihmissuhteiden paraneminen. Tutkimuksessa toteutunut musiikkiterapia voi toimia rooliltaan itsenäisenä kuntoutusmuotona tai osana muuta hoitokokonaisuutta. Se näyttäisi soveltuvan erityisesti henkilöille, joille taide on läheinen ilmaisuväylä. Tutkimusprojekti on johtanut ymmärtämään, kuinka musiikkiterapia voi siihen sitoutuneille olla kokonaisvaltainen, elämänkontekstin huomioiva ja siihen laadullisesti ja sisällöllisesti vaikuttava kuntoutusmuoto. Sen erityisyys on rikkaissa mahdollisuuksissa elämysten tuottamiseen merkittävien hetkien muodossa. Ne ovat vieneet terapiaprosessia eteenpäin ja olleet luomassa laadukasta elämää määrittelevää hyvinvoinnin tilaa.
Keywords: alcoholism; music therapy; musiikkiterapia; päihdeongelmaiset; kuntoutus; fysioakustinen menetelmä; fi=musiikkikasvatus|sv=musikpedagogik|en=Music Education|